Comparing the clinical efficacy and safety of high doses of beclomethasone inhaler with medium doses of beclomethasone inhaler combined with oral aminophylline or montelukast tablets in persistent asthmatic Iraqi patients. - Ali L. Jassim; Kassim J. Al-shamma; Zaid M. Kadhum; Falah H. AL-Salami (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2011)
Asthma is a chronic inflammatory disorder of the airways in which many cells and cellular elements play a role. The treatment guidelines recommend the use of a second controller drug in addition to medium doses of inhaled corticosteroids (ICSs) rather than the use of high doses ICS alone in the treatment of moderate-severe persistent asthma. This study was conducted to compare the clinical efficacy and safety of three treatment regimens in Iraqi patients with moderate-severe persistent asthma. The study included three groups; each group included 15 patients. Patients were administered beclomethasone inhaler alone 1500-2000 μg/day, beclomethasone inhaler 750-1000 μg/day plus oral controlled release aminophylline tablets 450 mg/day or beclomethasone inhaler 750-1000 μg/day plus oral montelukast tablets 10 mg/day for 4-5 weeks. Patients were followed 2 weeks and 4-5 weeks after the baseline visit. In all of the three groups, significant improvements were noticed in pulmonary function test parameters (FEV1, FVC, FEF50%) and the asthma symptom records (day-time symptoms, night-time symptoms, number of salbutamol puffs per 24 hours), while there were no significant differences among the groups. Regarding side effects, only the group of inhaled steroid plus aminophylline tablets showed discontinuation of drug therapy in some patients which could be attributed to the development of serious side effects. It was concluded that the administration of a second controller agent was important to use lower doses of inhaled beclomethasone. It was concluded also that montelukast was associated with a lower incidence of serious side effects than aminophylline which could make aminophylline an alternative to montelukast as combination therapy with medium doses ICS in the treatment of moderate-severe persistent asthma